2018
DOI: 10.1016/j.virol.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Live-attenuated bivalent measles virus-derived vaccines targeting Middle East respiratory syndrome coronavirus induce robust and multifunctional T cell responses against both viruses in an appropriate mouse model

Abstract: Cases of Middle East respiratory syndrome coronavirus (MERS-CoV) continue to occur, making it one of the WHO´s targets for accelerated vaccine development. One vaccine candidate is based on live-attenuated measles virus (MV) vaccine encoding the MERS-CoV spike glycoprotein (MERS-S). MV-MERS-S(H) induces robust humoral and cellular immunity against MERS-S mediating protection. Here, the induction and nature of immunity after vaccination with MV-MERS-S(H) or novel MV-MERS-N were further characterized. We focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…GLS-5300 is the first MERS coronavirus vaccine to advance into human trials. Among vaccine candidates in development, 22 four have started or will soon start phase 1 testing, including measles-vectored, 9,23 chimpanzee adenovirus-vectored, 24 and modified vaccinia Ankaravectored vaccines, all expressing full-length S-glycoprotein. [25][26][27] DNA vaccines and viral-vectored vaccines use recombinant technology that allows for rapid vaccine design in response to emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…GLS-5300 is the first MERS coronavirus vaccine to advance into human trials. Among vaccine candidates in development, 22 four have started or will soon start phase 1 testing, including measles-vectored, 9,23 chimpanzee adenovirus-vectored, 24 and modified vaccinia Ankaravectored vaccines, all expressing full-length S-glycoprotein. [25][26][27] DNA vaccines and viral-vectored vaccines use recombinant technology that allows for rapid vaccine design in response to emerging infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) and conferred protection to immunized animals upon pathogen challenge by lowering virus titers more than 100-fold (5). For MERS, we have demonstrated that both, high titers of neutralizing antibodies as well as effective and polyfunctional T cell responses, were induced in vaccinated animals (7,8) and conferred protection (7). Based on these data, a MeV-based MERS-vaccine candidate has been selected by the Coalition for Epidemic Preparedness Initiative (CEPI) for further clinical development (www.cepi.net/research_dev/our-portfolio).…”
Section: Introductionmentioning
confidence: 85%
“…Here, we explored the potential of recombinant MeV as vectors for the expression of the SARS-CoV-2 spike protein (S) as successfully applied for the development of MERS- (7,8) and SARSvaccine candidates (5,6) as well as numerous other pathogens (4). The S glycoprotein was chosen as antigen for its role as primary target of neutralizing antibodies (6,7) and the exemplary capability of MERS-CoV S protein to trigger strong cell-mediated immune responses when expressed by MeV in our front-runner MERS vaccine candidate (7,8). The SARS-CoV-2 S protein-encoding gene was inserted into two different positions of the MeV genome to modulate antigen expression, and both 4 recombinant MeV were successfully rescued.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the vector itself can serve as an adjuvant which in turn elicits both B-and T-cell responses (Ura et al, 2014). Finally, a wide variety of vector systems including measles viruses (Malczyk et al, 2015;Bodmer et al, 2018), Venezuelan equine encephalitis virus (VEEV) replicon system (Deming et al, 2006;Agnihothram et al, 2014;Zhao et al, 2016), adeno-associated virus (AAV) (Du et al, 2008), parainfluenza type 3 (BHPIV3) Bukreyev et al, 2004), human and chimpanzee adenovirus (hAd5 and ChAdOx1) (See et al, 2006(See et al, , 2008Kobinger et al, 2007;Kim et al, 2014;Guo et al, 2015;Hashem et al, 2019) and modified vaccinia virus Ankara (MVA) (Bisht et al, 2004;Czub et al, 2005;Kapadia et al, 2005;Haagmans et al, 2016) have been previously established for use as vaccine platforms for multiple infectious diseases. Herein, we will focus on the three systems that have been or are currently under clinical trial; all others are summarized in Table 1.…”
Section: Vector-based Vaccinesmentioning
confidence: 99%